The effect of shoot explant types of eleven stevia (Stevia rebaudiana Bertoni) accessions on in vitro growth - Suseno Amien; Arini Zahra Azhari; Citra Bakti; Haris Maulana (Jurnal Agro, 2021)
Explants play an important role in thepropagation system of stevia (Stevia rebaudiana Bertoni). A Completely Randomized Design (CRD) was used in this experiment with factorial pattern consisting of two factors, namely three types of explants (shoot tip, first node, and second node) and eleven accessions of stevia namely a1 (Bogor), a2 (Garut), a3 (Canada), a4 (Tawangmangu), a5 (STG1), a6 (SBG 4), a7 (SBG 10), a8 (SGB 2), a9 (BR5), a10 (SGR 7.5), a11 (TR 3.5). The results showed that shoot tip explant was the best explant than first node and second node for the number of shoots (18.11 shoots), number of leaves (93.49 leaves) and wet weight (3.56 grams). The best accession of shoot height was a10(SGR 7.5) (19.95 cm), the highest number of shoots wasa7(SBG 10) (21.87 shoots), the highest number of leaves wasa7(SBG 10) (138.00 leaves), the heaviest wet weight wasa7(SBG 10) (3.56 grams), the highest leaf chlorophyll content was a10 (SGR 7.5) (0.63 µg mL-1). Accessions with the fastest root initiation time at the rooting stage was a11 (TR 3.5) (4.00 DAC), the highest number of roots wasa10 (TR 3.5) (27.11 roots), the best root length wasa2(Garut) (4.51 cm). Information on the best explant types and stevia accessions in the in-vitro multiplication stage can be used as the basis for stevia breeding programs in Indonesia.AbstractEksplan berperan penting dalam sistem perbanyakan Stevia (Stevia rebaudiana Bertoni). Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) dengan pola faktorial yang terdiri dari dua faktor yaitu tiga jenis eksplan (ujung pucuk, ruas pertama, dan ruas kedua) dan sebelas aksesi stevia yaitu a1 (Bogor), a2 (Garut), a3 (Canada), a4 (Tawangmangu), a5 (STG1), a6 (SBG 4), a7 (SBG 10), a8 (SGB 2), a9 (BR5), a10 (SGR 7.5), a11 (TR 3.5). Hasil penelitian menunjukkan bahwa eksplan ujung pucuk merupakan eksplan terbaik dibandingkan buku pertama dan kedua untuk jumlah tunas (18,11 tunas), jumlah daun (93,49 daun) dan berat basah (3,56 gram). Aksesi terbaik pada tinggi pucuk adalah a10(SGR 7.5) (19,95 cm), jumlah pucuk tertinggi a7 (SBG 10) (21,87 pucuk), jumlah daun terbanyak a7 (SBG 10) (138.00 helai daun), bobot basah terberat a7 (SBG 10) (3,56 gram), kandungan klorofil daun tertinggi adalah GR 7,5 (0,63 µg mL-1). Aksesi dengan waktu inisiasi akar tercepat pada tahap perakaran adalah TR 3,5 (4,00 HST), jumlah akar terbanyak adalah TR 3,5 (27,11 akar), panjang akar terbaik adalah a2(Garut) (4,51 cm). Informasi jenis eksplan dan aksesi stevia terbaik pada tahap multiplikasi in-vitro dapat dijadikan dasar program pemuliaan stevia di Indonesia.